Facilitating Inclusion with Assistive Technology - Vafa, Shahrzad; Coombs-Richardson, Rita; Litton, Freddie (Social Science Learning Education Journal, 2018)
Technology is the driving force that will shape the future of our world, our nation, and our school systems, and the teaching /learning of all students. Assistive technology is meant to assist learning and to facilitate inclusion for all students. This paper examines the use of assistive technology in the classroom. It reviews different technology devices to assist students’ with their special needs.